Makna Simbolik dalam Arsitektur Pendopo Puro Mangkunegaran: Kajian Semiotika Budaya - Firman Hiwari; ⁠Susi Budi Astuti; Nayua Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to uncover the symbolic meanings embedded in the architectural elements and structure of the Pendopo Puro Mangkunegaran through a semiotic approach. Utilizing Roland Barthes' theory of semiotics, the analysis focuses on the denotative and connotative meanings of the building's form, spatial layout, and traditional Javanese ornamentation found in the pendopo. The findings reveal that Pendopo Puro Mangkunegaran represents Javanese cosmological values such as the relationship between humans and nature, spirituality, and social order. The pendopo is not merely a physical space but a cultural text containing ideological messages and the philosophical values of the Javanese community. This research also shows that semiotics can serve as an effective method in preserving traditional architecture by highlighting its profound meanings often overlooked in purely physical conservation approaches. These findings are relevant for the development of contextual architectural design based on local identity and the preservation of national cultural heritage.